THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE IN TEACHING VOCABULARY TO PRIMARY SCHOOL STUDENTS - Rosiana, Rosiana; Sulistyowati, Titis; Rismiyanto, Rismiyanto (Universitas Muria Kudus, 2025)
Abstract: Learning vocabulary is essential for English language learners and it is often best taught in early age, such as in primary school students. One of the methods that can be used in teaching vocabulary is Total Physical Response (TPR). The purpose of this study is to investigate the implementation of TPR in teaching vocabulary among primary school students and to explore the students’ responses after learning. The participants were an English teacher who also served as the researcher and twenty-three second-grade students of SD Aisyiyah Multilingual Darussalam Kudus. This study used a descriptive qualitative method, with data obtained from observation and interviews. The findings revealed that there are three teaching stages in the teaching vocabulary, such as pre-teaching, whilst-teaching, and post-teaching. Furthermore, the teacher has several roles in these stages, such as planner, director, model, and assessor. Various fun activities such as singing a song together, listening and doing, and playing games were used to boost the students’ enthusiasm and motivation. In the last stage, the teacher assesses the students to ensure their comprehension. In addition, interview data shows that TPR method has effectively helped students remember new vocabulary, create fun and enjoyable learning atmosphere.